Does inflation come and go in the same way? - Hukkinen, Juhana; Viren, Matti (SUERF - The European Money and Finance Forum, 2026)
The failure to predict the surge in inflation in 2021 raises questions about whether we are better equipped to anticipate a future decline in inflation. What tools do we intend to use for predicting the trajectory of inflation? Are we still primarily relying on survey data regarding inflation expectations, and are we still employing a Calvo-type structure to model inflation, in which only the intensive margin (the size of price increases) adjusts in response to changes in demand and supply? We would like to emphasize that our highly disaggregated consumer price data for the Euro area, consisting of 280 commodity categories, strongly suggests that price increases (inflation) are influenced not only by aggregate trends but also by sector-specific developments that result in state-dependent price adjustments. These factors may lead to more volatile fluctuations in the inflation rate. Furthermore, these reactions do not appear to be entirely symmetric when it comes to rising and falling inflation. When the inflation rate is close to zero, the role of state-dependent pricing is diminished, and nonlinearities become less significant.